Mitochondrial DNA quantity changes in leucocytes of cancer patients on cisplatin and 5-fluorouracil regimen - Khaing, Ei Phyo; Tun, Aung Win; Lertrit, Patcharee; Suthammarak, Wichit; Kaewsutth, Supannee; Kyaw, May Pyone (Institut Perubatan dan Pergigian Termaju (IPPT),Universiti Sains Malaysia, 2016)
Purpose: Cisplatin and 5-Fluorouracil are the critical components of therapeutic regimen in a broad range of malignancies. Their therapeutic efficacy is limited due to the development of toxic side effects and drug resistance by the cancer cells. Cisplatin toxic side effects are usually associated with mitochondrial injury in vivo and in vitro. In vitro evidence indicates that cisplatin decreases mitochondrial DNA (mtDNA) copy number. There is limited information on the effect of cisplatin on human mtDNA quantity. In order to clarify the effects of cisplatin and 5-FU on mtDNA in human, this study focused on the changes of mtDNA quantitation in cancer patients who were treated with cisplatin-based regimens. Methods: 24 blood samples from head and neck cancer patients were collected before chemotherapy and after second cycle of chemotherapy. Total DNA was extracted from peripheral blood leukocytes by salting out method. Validation of primer pairs were done by conventional PCR and checked by gel electrophoresis. The relative changes of mtDNA quantity were determined by quantitative PCR targeting Cyt-B genes normalizing with the nuclear gene PARL. Result: Comparing 24 samples, there was an increased mtDNA level after second cycle of chemotherapy, though it did Wilcoxon signed ranked test). However, 58% of the total patients had relatively increased mtDNA amount while 42% of the total patients showed decreased mtDNA amount after second cycle of chemotherapy (P<0.05, paired t-test). Conclusion: Overall, Cisplatin-based chemotherapy can affect mtDNA quantity changes in leucocytes of head and neck cancer patients.